2020
DOI: 10.1111/nan.12624
|View full text |Cite
|
Sign up to set email alerts
|

Novel CAPN3 variant associated with an autosomal dominant calpainopathy

Abstract: Appendix S1. Detailed genes panels and genes lists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 41 publications
6
39
1
2
Order By: Relevance
“…These findings clearly indicate that this variant is associated with autosomal dominant mild form of calpainopathy similar to previous reports of another in-frame deletion c.643_663del21 (p.Ser215_Gly221del) and missense c.1333G> A (p.Gly445Arg) variants with fatty degenerative changes in muscle. [2][3][4][5] As reported previously we identified this in-frame 15 bp deletion c.598_612del15 in total of 16 patients without a second pathogenic variant in CAPN3 indicating autosomal-dominant inheritance. 6 We fully agree that this in-frame 15 base pair deletion is associated with autosomal dominant mild form of calpainopathy.…”
Section: Dear Editorsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings clearly indicate that this variant is associated with autosomal dominant mild form of calpainopathy similar to previous reports of another in-frame deletion c.643_663del21 (p.Ser215_Gly221del) and missense c.1333G> A (p.Gly445Arg) variants with fatty degenerative changes in muscle. [2][3][4][5] As reported previously we identified this in-frame 15 bp deletion c.598_612del15 in total of 16 patients without a second pathogenic variant in CAPN3 indicating autosomal-dominant inheritance. 6 We fully agree that this in-frame 15 base pair deletion is associated with autosomal dominant mild form of calpainopathy.…”
Section: Dear Editorsupporting
confidence: 82%
“…The authors reported familial segregation analysis results along with phenotype, muscle MRI, and calpain 3 protein expression correlation studies in a family with heterozygous 15 base‐pair in‐frame deletion variant c.598_612del15 (p.Phe200_Leu204del) in CAPN3 . These findings clearly indicate that this variant is associated with autosomal dominant mild form of calpainopathy similar to previous reports of another in‐frame deletion c.643_663del21 (p.Ser215_Gly221del) and missense c.1333G> A (p.Gly445Arg) variants with fatty degenerative changes in muscle 2‐5 . As reported previously we identified this in‐frame 15 bp deletion c.598_612del15 in total of 16 patients without a second pathogenic variant in CAPN3 indicating autosomal‐dominant inheritance 6 .…”
supporting
confidence: 91%
“…This subclinical presentation is consistent with previous descriptions of autosomal dominant calpainopathies associated with the c.643_663del21 and the c.1333G>A CAPN3 variants. 2,6 Thus, by describing this additional family harboring the c.598_612del15 CAPN3 variant, we confirm the association of this eighth variant with autosomal dominant calpainopathies (or LGMDD4).…”
supporting
confidence: 70%
“…1B) as previously described in the literature. 6 Finally, familial segregation analysis was performed for the mother and the sister of the proband who harbor this same heterozygous CAPN3 variant (Fig.1A), presenting meanwhile with isolated moderate hyperCKaemia (respectively 285 UI/L and 148 UI/L CK levels). This subclinical presentation is consistent with previous descriptions of autosomal dominant calpainopathies associated with the c.643_663del21 and the c.1333G>A CAPN3 variants.…”
mentioning
confidence: 99%
“…While this manuscript was in preparation, the c.1333G> A p.(Gly445Arg) missense variant in CAPN3 was described in four unrelated French families presenting with a late onset form of mild dominant muscular dystrophy, and a c.1715G> C p.(Arg572Pro) variant was identified in another family with mild dominant muscular dystrophy. These were the first descriptions of missense CAPN3 variants associated with dominant disease [19,20].…”
Section: Introductionmentioning
confidence: 99%